Nanoparticle & luminescent ruthenium oligonucleotide conjugates - Keegan, Gemma (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
The field of plasmonies is a rapidly growing area of research and holds much promise for the improvement of diagnostics. The work in this thesis outlines the advances that have been made to assemble the components needed to prepare a potential sensitive DNA detection probe. This entails combining systems involving metal complexes (ruthenium complexes) with nanoparticles (triangular silver nanoplates) using DNA (oligonucleotides).
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.